The effects of five different types of planting medium on the growth performance of chilli / Fazidah Rosli ... [et al.] - Rosli, Fazidah; Muhammad, Khairul lkmal; Bula, Md Jamaluddin; Abdul Aziz, Noorshilawati; Abdullah, Nur Suraya; Mohammed, Anisah; Yusop, Mohamad Amir Shah; Nordin, Mohammad Ridhwan (2013)
The demand for chilli has increased tremendously in recent years. Chilli is a popular vegetable valued around the world for the color, flavor, spice. and nutritional value it contributes to many meals. Recently. the adverse effects of modern agriculture and the cause of several problems in environment have become a serious topic discussed. The objectives of this study is to evaluate the growth performance response of Capsicum annuum in five (5) different types of planting medium, and to determine the most suitable planting medium for the growth of chilli. The five (5) planting medium used were the Soil Mixture, Cocoa Peat, Organic Compost, burned Paddy Husk and also Empty Fruit Bunch. The experiment was conducted at Taman Herba. Unit Pengurusan Ladang, UiTM Pahang from Julai to October 2012 (13 weeks). The variety of Kulai (Line 15) and MC II were used in this experiment. A Randomized Completely Block Design (RCBD) with five (5) treatments and four (4) replications have been employed in this experiment. The data collected are plant height, number of leaves, fresh weight and dry weight of chilli. All the data was analyzed using the Microsoft Excel and Statistical Package for Social Science (SPSS). The result showed that the best treatment was obtained when using Soil Mixture and Cocoa Peat which gave good effect on the growth performance of chilli. But unfortunately, the result showed that Empty Fruit Bunch is not recommended to be used as planting medium for chilli plant because it does not show good performance for chilli growth.